Soil organic carbon dynamics under conservation agricultural systems - Franzluebbers, Alan J. (Agrociencia Uruguay, 2012)
Soil organic carbon (SOC) is a key element in the valuation of natural resources and the evaluation of how management affects soil quality and ecosystem services derived from soil. This paper describes a summary of some recent research aimed at understanding how SOC contributes to (a) various soil properties and processes, (b) global cycling of carbon, and (c) support of various ecosystem services. Stratiﬁed SOC with depth under conservation agricultural approaches helps soil function to an optimum. Conservation management approaches focusing on minimizing soil disturbance, maximizing soil cover, and stimulating biological activity can be achieved with different cropping choices and production goals in different environments all around the world. In the southeastern USA, SOC sequestration was 0.30 + 0.05 Mg ha-1 yr-1 in no-tillage systems without cover crop and 0.55 + 0.06 Mg ha-1 yr-1 in no-tillage systems with cover crop, suggesting that greater C input with increasing cropping system complexity of no-tillage systems will be beneﬁcial to SOC storage. The key to success for adoption of conservation agriculture will be to consider the agronomic, ecological, environmental, and economic constraints within a particular farm setting. On-going research continues to support the key contributions that enhanced SOC with conservation agricultural approaches can give to farmers and society.